Factors that predict mortality rate in biliary atresia - Al-Kawaz, Shatha A. (Journal of the Faculty of Medicine Baghdad, 2014)
Fac Med Baghdad2014; Vol.56, No.2Received: Feb. 2014Accepted March. 2014 Background: B.A is a relatively rare obstructive condition of the bile ducts causing neonatal jaundice. The etiology is unknown but is the result of a progressive obliterative process of variable extent.  If not treated, B.A is fatal within the first 2 years of life.Objectives: The aim of this study was to analyze & discuss the impact of many patients' factors on short-term outcome of patients with B.A who underwent Kasai operation in our department.Methods:  A prospective study on 34 patients with B.A surgically managed at pediatric surgical department /Medical City during the period Nov. 2006 to Sept. 2013. The patients were followed-up for 2-3 months and the outcome were evaluated by morbidity and mortality rates according to different patients' parameters (preoperative, intraoperative and postoperative factors) .Results: the mean age of the infants was (61.6 ± 8.1) days with a female to male ratio of 1.27:1. All the patients had type ш biliary atresia. Infants with body weight < 3.5 kg were about 10 folds more likely to die than those with body weight > 3.5 kg. Infants who passed greenish bowel motion at the 4th – 5th postoperative day were about 6 folds more likely to die p.value= 0.026. Infants with postoperative anastomotic leak were about 7 folds more likely to die than those with no leak p.value = 0.013. Strong highly significant correlation had been found among high death rate and reoperation rate (r = 0.78 and p < 0.001). of the thirty four infants, 24 (70.6%) survived, unfortunately, 10 infants (29.4%) died. the ratio of death to survive was 0.4: 1.Conclusions: the survival with native liver following drainage surgery for biliary atresia in our center, compared favorably with other international figures. Body weight, significant impaired liver function, severe associated anomalies, anastomotic leak and re-intervention, all, greatly contribute to increase mortality rate of those infants.